Disc formation in the collapse of supramassive neutron stars. Issue 4 (9th August 2018) - Camelio, Giovanni; Dietrich, Tim; Rosswog, Stephan
ABSTRACT: Short gamma-ray bursts (sGRBs) show a large diversity in their properties. This suggests that the observed phenomenon can be caused by different 'central engines' or that the engine produces a variety of outcomes depending on its parameters, or possibly both. The most popular engine scenario, the merger of two neutron stars, has received support from the recent Fermi and INTEGRAL detection of a burst of gamma rays (GRB170817A) following the neutron star merger GW170817, but at the moment, it is not clear how peculiar this event potentially was. Several sGRBs engine models involve the collapse of a supramassive neutron star that produces a black hole plus an accretion disc. We study this scenario for a variety of equations of states both via angular momentum considerations based on equilibrium models and via fully dynamical Numerical Relativity simulations. We obtain a broader range of disc forming configurations than earlier studies but we agree with the latter that none of these configurations is likely to produce a phenomenon that would be classified as an sGRB.